Pulmonary valve and right ventricular outflow tract surgery in adults: 23-year experience - Szczechowicz, Marcin; Mkalaluh, Sabreen; Farag, Mina; Loukanov, Tsvetomir; Karck, Matthias; Mashhour, Ahmed; Weymann, Alexander (Kardiologia polska, 2018)
Background: Surgery of the pulmonary valve, right ventricular outflow tract, and pulmonary artery falls under the domain of paediatric cardiac surgery. However, 97 adult patients underwent such operations in our institution from 1993 to 2016. Aim: This study aims to analyse preoperative risk factors, intraoperative data, postoperative outcomes, and long-term survival to identify the potential predictors of mortality and high-risk patients. - Methods: We divided our patient cohort into three groups in accordance with surgical indications: 17 patients with pulmonary valve endocarditis (group A), 70 patients with congenital defects involving the pulmonary valve (group B), and 10 patients who underwent pulmonary valve surgery for other indications, such as tumour or other acquired valvular disease (group C). - Results: Gender distribution was comparable in all the three groups, with about 40% of the total number of patients being female. The mean age was 35.9 ± 15.7 years. Sixty (61.9%) patients had a history of cardiac surgery. Various concomitant cardiac surgical procedures were necessary in 49 (50.5%) cases. There were two (11.8%) in-hospital deaths in group A, two (2.9%) in group B, and none in group C. Within the mean follow-up time of 6.6 ±7.2 years, three (17.7%) patients in group A, two (2.9%) in group B, and four (40%) in group C died. - Conclusions: Adult patients with pulmonary valve disease are often previously heart-operated and often need concomitant procedures. The operative risk in patients with pulmonary valve endocarditis is high. Surgery of congenital defects of the pulmonary valve is safe and can be performed with excellent outcomes.
Published: December 15, 2017
Gesehen am 02.05.2019